Impairment of diastolic function during short-term anthracycline chemotherapy. Issue 1 (January 1995) - Cottin, Y.; Touzery, C.; Coudert, B.; Gilles, A.; Walker, P.; Massing, J. L.; Toubeau, M.; Riedinger-Berriolo, A.; Caillot, D.; Louis, P.
Abstract : OBJECTIVE--To assess the early changes in left ventricular diastolic and systolic function due to anthracycline treatment. DESIGN--A prospective study of cardiac function by radionuclide angiography in adults before and one month after the end of anthracycline treatment. PATIENTS--60 patients without cardiac disease treated with chemotherapy containing anthracycline. METHODS--Cardiac function was assessed by radionuclide measurement throughout treatment. Ejection fraction, peak ejection rate, time to peak ejection rate, filling rate, and time to peak filling rate were measured before and after treatment. To normalise radionuclide measurements of the left ventricular diastolic function the ratio of the filling rate to the ejection fraction and the ratio of the filling rate to the peak ejection rate were calculated. RESULTS--No patient developed symptomatic congestive cardiac failure. The ejection fraction decreased from 58% (5%) to 55% (6%) (P < 0.001), the peak ejection rate fell from 2.99 (0.41) to 2.77 (0.41) of the end diastolic volume per second (P < 0.001), and the peak filling rate from 2.71 (0.47) to 2.55 (0.44) of the end diastolic volume per second (P < 0.01) after treatment. No difference was observed in the normalised ratios. CONCLUSIONS--This report shows simultaneous impairment of left ventricular systolic and diastolic radionuclide parameters. The absence of variation in normalised measurements suggests similar changes in ejection fraction, peak ejection rate, and peak filling rate throughout treatment.